Study on Dynamic Mechanical Properties and Damage Evolution Model of Siltstone - Guoliang Zhang; Haipeng Jia; Shuaifeng Wu (Shock and Vibration)
This paper is focused on exploring the dynamic mechanical properties and damage process of siltstone. For this purpose, different stress wave wavelengths (0.5 m∼2.0 m) and different strain rates (25 s−1∼120 s−1) were applied to siltstone specimens in the SHPB dynamic impact test. The experimental results show that the dynamic compressive strength of siltstone is linearly positively correlated with the strain rate, and the dynamic increase factor is linearly positively correlated with the natural logarithm of strain rate; the peak strain is linearly positively correlated with the strain rate, and the increase in wavelength causes the peak strain to increase. Through multiple impact tests, it is concluded that the cumulative damage to siltstone increases with the number of impacts. The cumulative damage curve exhibits an initial rapid rise, followed by a stable development, followed by another rapid rise. With increasing wavelength of the stress wave, the stable development of the curve gradually decreases, the cumulative damage to the siltstone is intensified, and the number of repeated impacts is reduced. Meanwhile, a model for damage evolution is established based on the inverse of the Gompertz function, and the physical meanings of the model parameters are determined. The model can reflect the influence of both stress wave parameters and impact times. Verification of the model demonstrates the rationality of the model and the correctness of the physical meaning of the parameters. The model could be applied in future studies of damage to sedimentary rocks.